Unitary Caring Science - Universals of Human Caring and Global Micro practices of Caritas. - Jean Watson (OPI Napoli, 2019)
This manuscript offers a reflective pause to consider an overview of Unitary Caring Science as a philosophical-theoretical discipline-specific, professional nursing practice/praxis model for human caring nursing. It provides the background of the 10 Caritas Processes, considered universals of human caring phenomena and practices. The underlying starting point for unitary caring science is informed by an 'Ethic of Belonging '- that is, we all belong to the infinite field and sacred circle of life itself. - belonging to the cosmic energy of universal Love. Thus our 'Belonging' becomes before our separate 'Being'. So, in this foundational unitary starting point - 'ethics comes before ontology'. With this philosophical-ethical foundation nursing practice moves from technical industrial forms of practice to Praxis, that is discipline specific, value guided, informed, knowledgeable, moral practice (praxis). This shift transcends technology and objective task- focused- physical care, to critiquing, repatterning practices from tasks and skills to Caring -Healing Arts and micro-practices that allow for human face- to- face, heart- to- heart - energetic human caring touch and transpersonal caring moments that unite.